Stability of haematological parameters and its relevance on the athlete's biological passport model - Lombardi, G.; Lanteri, P.; Colombini, A.; Lippi, G.; Banfi, G. (Sports Medicine, 2011)
The stability of haematological parameters is crucial to guarantee accurate and reliable data for implementing and interpreting the athlete's biological passport (ABP). In this model, the values of haemoglobin, reticulocytes and out-of-doping period (OFF)-score (Hb-60vRet) are used to monitor the possible variations of those parameters, and also to compare the thresholds developed by the statistical model for the single athlete on the basis of its personal values and the variance of parameters in the modal group. Nevertheless, a critical review of the current scientific literature dealing with the stability of the haematological parameters included in the ABP programme, and which are used for evaluating the probability of anomalies in the athlete's profile, is currently lacking. In addition, we collected information from published studies, in order to supply a useful, practical and updated review to sports physicians and haematologists.